The Coronavirus Conversation on Reddit: A Mixed Methods Approach - Ilir Rama (Culture e Studi del Sociale)
This article engages in a methodological discussion on how to consider affordances in the context of digital environments, focusing on the r/coronavirus community on Reddit. To underline how affordances might affect social interaction, Reddit and its voting system offer a privileged ground to observe how social dynamics intersect with technical features to guide expression. I will consider a vast dataset of comments, including those deleted by their own authors, through non-participant ethnographic observation and automated text analysis. It is shown how the r/coronavirus community fluidly negotiates social norms by enforcing them through affordances, that are employed to sanction social behaviour that does not conform to broader situated cultural norms. This intertwines with moderation practices, as they concur to define what is considered socially proper within an environment, as well as functioning as discursive tools to legitimise a specific view of the world. Based on this experience, the implications of a mixed methods approach for the study of online communities are briefly presented, underlining how it might aid reflexivity for researchers embedded in their research environment.